Carbapenem Resistant Pseudomonas Aeruginosa: A Multicenter Study on Prevalence, Distribution, and Risk Factors across Six Health Facilities in Yaoundé, Cameroon - KAMENI, Georgette Njila; Lyonga Mbamyah, Emilia; Moni Ndedi , Esther Del Florence; Nganou Kamgang, Ines Dalia; Mondinde Ikomey, George; Yengo Kunkeng, Clauvis; Tongo Mesembe, Martha; Elimbi, Neline Yameni; Kameni, Mary Ngongang; Taya Fokou, Jean Bosco; Ohene Amofa, Justice; Noubissi Toyim , Albert; et al. (International Journal of Medical Science and Clinical Research Studies, 2025)
Carbapenem-resistant Pseudomonas aeruginosa is a significant public health threat, especially in low and middle-income countries. These strains are known to cause outbreaks, and their isolation continues to increase, further limiting therapeutic options. In Cameroon, however, there is limited data on the resistance profiles of circulating Carbapenem-resistant Pseudomonas aeruginosa strains. This study aimed to determine the prevalence, distribution and susceptibility profile of Carbapenem-resistant Pseudomonas aeruginosa isolates from six health facilities in Yaoundé, Cameroon. An analytical cross-sectional study was conducted over nine months (November 2023–July 2024). Carbapenem-resistant Pseudomonas aeruginosa isolates from clinical specimens were collected and re-identified. After culturing on cetrimide and nutrient agar, biochemical identification was done using the API 2ONE system. Antimicrobial susceptibility testing was performed to assess resistance to carbapenems and other antibiotics. Carbapenemase and extended-spectrum Beta-lactamases production in Carbapenem resistant Pseudomonas aeruginosa was detected using the Carbapenem inhibition and combined disc methods. Of the 217 isolates, 125 (representing 57.6%) were confirmed as Pseudomonas aeruginosa, with 31.2% (39/125) resistant to carbapenems. Among these, 48.7% (19/39) were resistant to imipenem, and 51.3% (20/39) were resistant to meropenem. Carbapenemase production was observed in 46.2% (18/39), while coproduction of carbapenemase and extended-spectrum Beta-lactamases was observed in 28.20% (11/39). High resistance was also seen to cephalosporins (54.4%) and penicillin (59.2%). A majority of Carbapenem-resistant Pseudomonas aeruginosa isolates had a multiple antibiotic resistance index ≥ 0.2. This study underscores the growing public health concern posed by Carbapenem-resistant Pseudomonas strains. Enhanced surveillance is crucial to curb the dissemination and spread of these strains.